The power of servant-leadership - Greenleaf, Robert K. (Berrett-Koehler Publishers, 1998)
Based on the seminal work of Robert K. Greenleaf, a former AT & T executive who coined the term almost thirty years ago, servant-leadership emphasizes an emerging approach to leadership-one which puts serving others, including employees, customers, and community, first. The Power of Servant Leadership is a collection of eight of Greenleaf's most compelling essays on servant-leadership. These essays, published together in one volume for the first time, contain many of Greenleaf's best insights into the nature and practice of servant-leadership and show his continual refinement of the servant-as-le.